2010
DOI: 10.1111/j.1742-4658.2010.07717.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal growth‐inhibitory factor (metallothionein‐3): reactivity and structure of metal–thiolate clusters*

Abstract: Metallothionein‐3, also called neuronal growth‐inhibitory factor, is one of the four members of the mammalian metallothionein family, which in turn belongs to the metallothionein, a class of ubiquitously occurring low‐molecular‐weight cysteine‐ and metal‐rich proteins containing metal–thiolate clusters. Mammalian metallothioneins contain two metal–thiolate clusters of the type M(II)3‐Cys9 and M(II)4‐Cys11 [or Cu(I)4‐CysS6‐9]. Although metallothionein‐3 shares these metal clusters with the well‐characterized me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 45 publications
1
49
0
Order By: Relevance
“…The apo-Mt3 form (i.e. with no bound metal) is predominantly unstructured and unable to support activity; thus, the metal binding status of Mt3 is important for its biochemical and physiological activity (33). In this context, we found that removal of zinc also rendered Mt3 and peptide 1 completely incapable of promoting actin polymerization or dis- sociating c-Abl from F-actin, suggesting that zinc binding is essential for the Mt3 effects described here.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The apo-Mt3 form (i.e. with no bound metal) is predominantly unstructured and unable to support activity; thus, the metal binding status of Mt3 is important for its biochemical and physiological activity (33). In this context, we found that removal of zinc also rendered Mt3 and peptide 1 completely incapable of promoting actin polymerization or dis- sociating c-Abl from F-actin, suggesting that zinc binding is essential for the Mt3 effects described here.…”
Section: Discussionmentioning
confidence: 69%
“…Mt3 and peptide 1 have "zinc-binding motifs" (31)(32)(33)(34). Hence, we examined whether the binding of zinc was required for the effects of Mt3 and/or peptide 1.…”
Section: Mt3-induced Actin Polymerization and Dissociation Of C-abl Fmentioning
confidence: 99%
“…MT-3 represents a unique metalloprotein called also neuronalgrowth inhibitory factor, which inhibits the outgrowth of neuronal cells (Huang, 2010). In comparison with MT-1 and MT-2, MT-3 shows distinct chemical, structural, and biological properties (Faller, 2010;Ding et al, 2010;Brewer, 2009;Bofill et al, 2009;Ba et al, 2009). Moreover, the connection of MT-3 to neurodegenerative processes is discussed.…”
Section: Mtsmentioning
confidence: 98%
“…Metallothioneins (MTs) are intracellular, low molecular weight proteins containing an array of conserved 20 cysteines and polynuclear metal-sulfur coordination sites formed by metal ions [1,2]. Their most widely detected isoforms in mammals, MT-1 and MT-2, are rapidly induced in the liver by a wide range of metals, drugs, and inflammatory mediators [3].…”
Section: Introductionmentioning
confidence: 99%